Augmented Reality Realitas Augmentasi sebagai Media Pembelajaran Interaktif pada Material Gelombang Cahaya: Tinjauan Pustaka - Windha, Windha; Marlina, Leni; Siahaan, Sardianto Markos (EduFisika: Jurnal Pendidikan Fisika, 2025)
This study aims to analyze the effectiveness of Augmented Reality (AR) as an interactive learning medium for understanding light wave concepts in physics. Using a systematic literature review of national and international studies published between 2019 and 2025, this research synthesizes evidence on AR’s role in improving students’ conceptual understanding and critical thinking. Unlike previous reviews that focused on general AR applications in science education, this study specifically examines its pedagogical impact on the light wave topic, which remains underexplored despite its abstract and complex nature. The review reveals that AR enhances visualization of light phenomena, fosters active and engaging learning environments, and supports 21st-century skills such as creativity, collaboration, and problem-solving. However, its implementation still faces challenges related to infrastructure, teacher readiness, and content development. Overall, this study provides a novel synthesis that highlights AR’s distinctive potential to bridge the gap between abstract theory and concrete experience in learning physics, offering new insights for educators and researchers on topic-specific AR integration.